2019
DOI: 10.3389/fpsyg.2019.02439
|View full text |Cite
|
Sign up to set email alerts
|

Different Aspects of Emotional Awareness in Relation to Motor Cognition and Autism Traits

Abstract: Emotion is inherently embodied, formulated through bodily sensation, as well as expressed and regulated through action. Both expressing one’s own emotions and understanding the emotional actions of others are common areas of difficulty in autism. Moreover, reduced emotional awareness is also thought to be problematic in autism, and such difficulties may be mediated by impaired motor cognition. We aimed to examine how intensity of emotional experience and ability to differentiate between one’s own emotions rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Research on emotion differentiation has found that autistic and non-autistic individuals with elevated autistic traits make less subtle distinctions between negative emotions than do neurotypical individuals (Erbas et al, 2013; Huggins et al, 2019). Emotion differentiation refers to the ability to make fine-grained, nuanced distinctions between similar emotions, with lower emotion differentiation linked to poorer well-being (Smidt & Suvak, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research on emotion differentiation has found that autistic and non-autistic individuals with elevated autistic traits make less subtle distinctions between negative emotions than do neurotypical individuals (Erbas et al, 2013; Huggins et al, 2019). Emotion differentiation refers to the ability to make fine-grained, nuanced distinctions between similar emotions, with lower emotion differentiation linked to poorer well-being (Smidt & Suvak, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PED-Task outcomes have been partially reported in another publication (Huggins et al, 2019), so we do not want to report them here. The only outcome of interest is that neither negative, r (87) = −.085, p = .428, nor positive, r (82) = −.003, p = .978, differentiation significantly correlated with total inconsistency scores.…”
Section: Resultsmentioning
confidence: 99%
“…Participants also completed a version of the PED-task (Erbas et al, 2014), the results of which are included in another publication (Huggins, Cameron, & Williams, 2019) and thus will not be elaborated on in detail here. The only outcome of interest for the PED-task was emotion differentiation scores, reflecting how well participants differentiated between similar emotional states.…”
Section: Other Outcomesmentioning
confidence: 99%
“…Additionally, while we showed convergent validity for the AFQ-NL in the neurotypical population, no correlation between AFQ and AQ was found in the ASC population. The originally reported correlation between AFQ and autistic traits was found in neurotypicals (Huggins et al, 2019) and we expected that correlation to extend to ASC individuals. However, AQ may not have been the best variable to calculate convergent validity for the ASC population.…”
Section: Limitationsmentioning
confidence: 90%